TILT: a randomized controlled trial of interruption of antiretroviral therapy with or without interleukin-2 in HIV-1 infected individuals. - Angus, B; Lampe, F; Tambussi, G; Duvivier, C; Katlama, C; Youle, M; Williams, I; Clotet, B; Fisher, M; Post, F; Babiker, A; Phillips, A (2008)
OBJECTIVE: We aimed to see if structured treatment interruption (STI) could be supported safely with the use of two cycles of IL-2 (4.5 MIU q12h subcutaneously 5 days) before STI to prolong the time before therapy restarted. METHODS: Subjects were randomly allocated to either A - continuous ART; B - continue for 9 weeks, then STI; restart with the same ART when the CD4 count falls below 200 cells; or C - two cycles of IL-2, 8 weeks apart, while still on ART; at week 9 stop ART and use a new cycle of IL-2 alone whenever the CD4 count falls < 300 cells. Patients were followed until week 105. RESULTS: 86 mostly white middle aged homosexual men with a baseline median CD4 count of 754 cells/ml (range 240-1400) and a nadir CD4 count of 268 cells/ml (range 62-822) enrolled. By 96 weeks there was a 66% probability of having restarted ART in arm B compared with 34% in arm C (p = 0.002; log rank test). New drugs were used in 60% in arm A, 57% in arm B and 45% in arm C. 4 subjects had a dose modification in the first cycle due to toxicity with 2 interrupting. There were 39 SAEs with 21 in arm C. There were no deaths. CONCLUSIONS: The primary aim of the trial was to gain experience in using IL-2. IL-2 delayed restarting drugs and fewer new drugs were used.